Bibliometric Analysis: Augmented Reality Research Trends in Indonesia in Biology Learning - Asrizal Wahdan Wilsa; Sutikno Sutikno; Dyah Rini Indriyanti; Jaja Jaja (Jurnal Penelitian Pendidikan IPA, 2023)
This article aims to analyze the trend of Augmented Reality (AR) research in Indonesia in learning biology through bibliometric analysis sourced from Google Scholar and Scopus in 2013-2022. The sample articles obtained were 223 articles. The results show that AR research in biology learning in Indonesia will increase in 2019-2021 and will decrease in 2022. Universitas Pendidikan Indonesia and Universitas Negeri Malang rank first and second in publications regarding AR in biology learning in Indonesia. The results of the data visualization analysis consist of 7 clusters, namely the use of AR applications in research related to biology learning, AR relationship with learning materials, educational level, and learning outcomes, and evelopment and application of AR in biology learning. Furthermore, the fourth to seventh clusters are clusters which show that research on AR still has opportunities to be carried out related to the use of AR applications in biology learning in Indonesia